5'-Nucleotidase and adenosine deaminase in patients with rheumatoid arthritis - Zivkovic, Nela K; Djindjić, Boris; Stojanović, Sonja; Krstić, Ivana; Ćirić, Ivana; Kostić, Tomislav; Kocić, Gordana (Vojnosanitetski pregled, 2017)
Background/Aim. The essence of rheumatoid arthritis (RA) pathogenesis is inflammation, modification of immune system and cell damage. 5'-nucleotidase (5'-NT) and adenosine deaminase (ADA) have a significant role in the process of inflammation-caused tissue damage. The aim of the study is to define 5'-nucleotidase and adenosine deaminase activity in serum of patients with RA treated with methotrexate (MTX) and patients with RA who were not treated with methotrexate, as well as to determine the correlation between the enzymes’ activities and the disease activity. Methods. The study included 160 patients suffering from RA, 60 of them were not treated with methotrexate (average age 56.8 years; 68.3% female) and 100 patients were treated with methotrexate (average age 59.8 years; 88% female), as well as 60 healthy controls (average age 58.8; 66.6% female). Patients suffering from chronic inflammatory diseases, chronic respiratory, cardiac and kidney insufficiency, severe acute diseases and other diseases which might modify inflammatory response were not included in the study. Results. There was no statistically significant difference in 5'-NT values among groups. ADA values were significantly different in all tested groups. Post-hoc analysis (Dunnett’s T3 test) showed that ADA activity in RA groups was significantly higher as compared to that in the control group (p < 0.001), and that ADA activity in the RA group with MTX was significantly smaller as compared to RA group without MTX (p < 0.001). There was not significant correlation between the disease activity and activities of tested enzymes. Conclusion. We concluded that adenosine deaminase activity was increased in patients with rheumatoid arthritis, as well as that the application of methotrexate led to the decrease of this enzyme activity in the serum of patients with rheumatoid arthritis. The activity of 5'-nucleotidase is not increased in patients with rheumatoid arthritis and did not depend on methotrexate treatment. Serum adenosine deaminase and 5'-nucleotidase activities are not good indicators of rheumatoid arthritis activity.
Keywords: arthritis; rheumatoid; adenosine deaminase; 5'-nucleotidase